Altered Expressions of Transfer RNA-Derived Small RNAs and microRNAs in the Vitreous Humor of Proliferative Diabetic Retinopathy - Yang, Yan; Yue, Wenyun; Wang, Nan; Wang, Zicong; Li, Bingyan; Zeng, Jun; Yoshida, Shigeo; Ding, Chun; Zhou, Yedi (Frontiers in Endocrinology, 2022)
Purpose: We sought to reveal the expression profiles of transfer RNA-derived small RNAs (tsRNAs) and microRNAs (miRNAs) in the vitreous humor of patients with proliferative diabetic retinopathy (PDR). Methods: Vitreous humor samples were obtained from PDR patients and a control group for this study. Sequencing of small RNAs was conducted to assess the expression profiles of tsRNAs and miRNAs in both groups, which was followed by validation using real-time quantitative polymerase chain reaction (RT-qPCR). Bioinformatics analyses were conducted to predict the target genes and their potential biological functions and signaling pathways. Results: A total of 37 tsRNAs and 70 miRNAs with significant differences were screened out from the vitreous humor samples of PDR patients compared to controls. Following validation by RT-qPCR, the target genes of the validated tsRNAs and miRNAs were predicted, and Gene Ontology analysis indicated that the target genes of the tsRNAs were most enriched in the cellular macromolecule metabolic process, cytoplasm, and ion-binding, while those of the miRNAs were most abundant in the regulation of major metabolic process, cytoplasm, and protein-binding. In addition, Kyoto Encyclopedia of Genes and Genomes pathway analysis showed that the target genes of said tsRNAs and miRNAs were most enriched in the adenosine monophosphate-activated protein kinase signaling pathway and Th17 cell differentiation, respectively. Conclusions: The present study identified altered tsRNAs and miRNAs in vitreous humor samples of PDR patients, which may play important roles in the pathogenesis of PDR and could be considered potential therapeutic targets in the treatment of PDR.